2016
DOI: 10.1186/s12913-016-1521-4
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of health promotion and disease prevention interventions addressed to elderly people

Abstract: BackgroundThe ageing of modern societies remains one of the greatest challenges for health and social systems. To respond to this challenge, we need effective strategies assuring healthy active life for elderly people. Health promotion and related activities are perceived as a key intervention, which can improve wellbeing in later life. The main aim of this study is the identification and classification of such interventions addressed to older adults and elderly. Therefore, the strategy based on the scoping re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 14 publications
3
28
0
Order By: Relevance
“…The present study was based on scoping review methodologies designed in the last five years (2015-2019), with the purpose of identifying and reviewing the effectiveness of different interventions addressing elderly health promotion and related areas. This study is a continuation of the research of Duplaga et al [4]. The concept of the scoping review in the present study follows that of previous scoping review studies, such as Arksey and O'Malley [6], and further discussion by Levac, Colquhoun, and O'Brien et al [6].…”
Section: Methodssupporting
confidence: 56%
See 3 more Smart Citations
“…The present study was based on scoping review methodologies designed in the last five years (2015-2019), with the purpose of identifying and reviewing the effectiveness of different interventions addressing elderly health promotion and related areas. This study is a continuation of the research of Duplaga et al [4]. The concept of the scoping review in the present study follows that of previous scoping review studies, such as Arksey and O'Malley [6], and further discussion by Levac, Colquhoun, and O'Brien et al [6].…”
Section: Methodssupporting
confidence: 56%
“…The classification for the interventions methods followed Duplaga et al [4] and was divided into four categories: health promotion (HP), primary prevention (PP), screening (SC), and social support (SS).…”
Section: Intervention Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a recently published scoping review only found nine studies combining health promotion and social support, several among them addressing a general population or persons aged <65 years. 29 Consequently, it is clear that loneliness, social network, and social support are important aspects to target in health-promoting interventions for older persons, and to evaluate such initiatives. Accordingly, seeking to support advancement of knowledge on this subject, the aim of the present study was to evaluate the 1-year effect of the health-promoting intervention senior meetings for older community-dwelling persons on loneliness, social network, and social support.…”
Section: Introductionmentioning
confidence: 99%